User Experience Design Analysis of the Karawang Job Vacancy Website using the User-Centered Design Method and System Usability Scale - Sopian, Jajang; Huda, Baenil; Novalia, Elfina; Hananto, April Lia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
An optimized User Experience (UX) design plays a significant role in creating a comfortable browsing experience, ensuring good accessibility, and enhancing user satisfaction. This study analyzes the UX design of the Info Loker Karawang website by applying the User-Centered Design (UCD) method and evaluating the resulting prototype using the System Usability Scale (SUS) to assess the website’s ease of use. The UCD method was selected because it places the user at the center of the design process, enabling the development of solutions that align closely with users’ needs, expectations, and characteristics. This approach has proven effective in producing relevant and intuitive interfaces through stages of analysis, design, and evaluation involving active user participation. Following the design phase, the prototype was tested using the SUS instrument to measure how well the design solution met usability and user satisfaction criteria. The evaluation results indicate that applying UCD in website design significantly improves usability, achieving a SUS score of 72.5, which falls into Grade B and is categorized as “Good” on the adjective rating scale. This research provides insights into the importance of user-centered approaches in website development and demonstrates the effectiveness of SUS in evaluating and measuring the success of UX design outcomes.